2015
DOI: 10.1073/pnas.1508735112
|View full text |Cite
|
Sign up to set email alerts
|

DNA capture reveals transoceanic gene flow in endangered river sharks

Abstract: For over a hundred years, the "river sharks" of the genus Glyphis were only known from the type specimens of species that had been collected in the 19th century. They were widely considered extinct until populations of Glyphis-like sharks were rediscovered in remote regions of Borneo and Northern Australia at the end of the 20th century. However, the genetic affinities between the newly discovered Glyphis-like populations and the poorly preserved, original museum-type specimens have never been established. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 44 publications
1
77
0
Order By: Relevance
“…The Speartooth Shark, Glyphis glyphis (Carcharhinidae), belongs to a poorly known and highly threatened group of river sharks, whose taxonomy, distributions, population structure and conservation status are only now beginning to be resolved (Pillans et al 2010;Feutry et al 2014;Li et al 2015;White et al 2015). Glyphis glyphis is of high conservation concern and is classified as critically endangered on the Australian Environment Protection and Biodiversity Conservation Act 1999.…”
Section: Introductionmentioning
confidence: 99%
“…The Speartooth Shark, Glyphis glyphis (Carcharhinidae), belongs to a poorly known and highly threatened group of river sharks, whose taxonomy, distributions, population structure and conservation status are only now beginning to be resolved (Pillans et al 2010;Feutry et al 2014;Li et al 2015;White et al 2015). Glyphis glyphis is of high conservation concern and is classified as critically endangered on the Australian Environment Protection and Biodiversity Conservation Act 1999.…”
Section: Introductionmentioning
confidence: 99%
“…remain a critical knowledge gap, studies from Australia and Papua New Guinea indicate that adults can occur outside of rivers in coastal marine environments (Pillans et al ., ; White et al ., ). In fact, it is possible that adults may travel long distances with recent molecular data indicating contemporary gene flow between the populations of G. gangeticus in Myanmar (= G. siamensis ), Borneo (= G. fowlerae ) and those of India and Pakistan, suggesting marine dispersal of several thousand km (Li et al ., ).…”
mentioning
confidence: 97%
“…Prior to taxonomic resolution by Li et al . (), there were thought to be five species in the genus Glyphis . However, molecular data confirmed that the Borneo river shark Glyphis fowlerae Compagno, White & Cavanagh 2010 from the Kinabatangan River, Sabah, Malaysian Borneo and the Irrawaddy river shark Glyphis siamensis (Steindachner 1896) from the Irrawaddy River, Myanmar, are junior synonyms of the Ganges shark Glyphis gangeticus (Müller & Henle 1839).…”
mentioning
confidence: 99%
See 2 more Smart Citations